A role of blood plasma cytokines in mice with B16 melanoma - A. N. Egorov; A. S. Golderova; R. A. Gotovtsev; I. P. Troev; I. E. Nikolaeva (Медицинская иммунология)
The role of cytokines in regulating the immune response and tumor progression is an important aspect of studies in oncology. B16 melanoma is characterized by an aggressive course and a high level of metastasis, which requires a deep understanding of the mechanisms involved. The purpose of this study was to study the level of cytokines in the blood plasma of mice with B16 melanoma. The experiment used C57BL/6 mice injected with B16-F10 melanoma cells. The animals were divided into two groups: control and experimental. Levels of key cytokines such as IFNg, TNFa, IL-6 and IL-10 were monitored for 21 days using enzyme-linked immunosorbent assay (ELISA). The results of the study showed a significant increase in the level of IFNg and TNFa cytokines in the blood plasma of mice from the experimental group compared to the control group. It should be noted that both IFNg and TNFa play a key role in stimulating macrophages and neutrophils for more effective killing of tumor cells. This cytotoxic response helps suppress tumor growth and metastasis. Elevated levels of IL-6 indicate the development of an inflammatory response. Although this cytokine at certain doses may reduce inflammation, excessive IL-6 can promote the growth and more aggressive behavior of tumors. Reduced levels of IL-10 can increase inflammation and weaken the body’s immune response against tumors. Thus, the balance between various cytokines plays a crucial role in regulating the immune response to cancer cells and determines the nature of tumor progression. At the same time, the level of IL-10, a cytokine with antiinflammatory properties, was reduced in the experimental group, thus indicating an imbalanced regulation of immune response. Thus, the data obtained demonstrate that development of B16 melanoma is associated with significant changes in the blood plasma cytokine profile which may play a key role in the pathogenesis of the disease. These results highlight the importance of further research to develop new therapeutic strategies aimed at modulating the cytokine response in melanoma.